Whose News? Investigating Power Relations Between Journalists and Public Relations Practitioners - Sissons, Helen (Auckland University of Technology, 2015)
The interactions between journalists and public relations practitioners directly and indirectly influence the news that citizens consume. In fact, this thesis finds the interdependence between public relations and journalism in New Zealand is extensive enough to call journalists and PRPs content siblings, together constructing the news we all rely on to make decisions about our lives. However, the relationship is not one of equals with evidence of media and information management clear in both the products of the relationship and the interactions between the two practices. Recent research has shown that at least half of all news stories are based wholly or in large part on public relations material and journalists are now reliant on such information to fill the “news hole”. The aim of this study was to examine the day-to-day practices of journalists and public relations practitioners in New Zealand and investigate in detail how interactions between them affected the news product, with a particular emphasis on which practice held the initiative. In order to achieve the research objective, the researcher applied innovative video-ethnographic methods and textual analysis to an examination of the practices and their outputs. The study took the perspective of the practitioners and the processes they employed in their everyday routines, which is an area underexplored by researchers. The study captured rare footage of journalists and PRPs interacting and through analysis of verbal and non-verbal actions, demonstrated journalists’ increasing difficulties in accessing information, even in publicly funded organizations, without going through public relations spokespeople. While it is known that this reliance is potentially damaging to the quality of the news product, the research provided new evidence that it may also be unhelpful at an individual level for journalists and PRPs, requiring them to be less than open and honest in their dealings. The findings showed that an over-reliance on public relations’ materials by journalists is weakening journalism’s traditional investigative role. Further, the power relations between journalists and public relations practitioners favour PRPs, allowing them opportunities deliberately to restrict media access to information in order to control the tone and/or the substance of the media coverage. What should be of concern to scholars, particularly scholars of public relations, is that the data presented here contradict what many in public relations would like to believe, that it is about creating understanding, building relationships and ensuring management is informed about and responsive to public opinion. What this study has demonstrated is that public relations is still about working on behalf of organisations to control what information is released, including the finessing of negative reports, the blocking of legitimate public debate and the influencing of public opinion for the good of the organisation.
Keywords: Journalism; Public relations; Ethnography; Non-verbal communication; Media discourse